Assessment of effect of chronic alcohol intoxication on certain parameters of the autonomic nervous system and cognitive functions - R. N. Аkalaev; V. Kh. Sharipova; A. A. Stopnitskiy; Kh. Sh. Khozhiev (Вестник анестезиологии и реаниматологии)
The objective of the study: to study certain parameters of the autonomic nervous system (ANS) and cognitive functions in patients with acute alcohol intoxication of different severity degrees. Subjects and methods. 312 patients with acute alcohol intoxication and chronic alcohol abuse were enrolled in the study. Manifestations, medical history, the duration of drinking bout, ethanol blood level were assessed. Blood panel included ALT, AST, LDH, and blood levels of free ammonia, lactate, and medium molecules. The subjects were divided into three groups: Group I - 78 patients with severe alcohol intoxication, Group II – 166 patients with moderate alcohol intoxication, and Group III – 68 patients with mild alcohol intoxication. The state of ANS was assessed according to the following indicators: heart rate, systolic and diastolic blood pressure, Kerdo vegetative index, and results of cardiointervalography by R.M. Baevsky (1986). The severity of intellectual impairment was assessed using the ММSE scale for 10 positions, the FAB scale for 6 positions, as well as the Reitan test in seconds on the 1st day. Results. In patients of Group I, the alcohol level was 1.5 and 1.35 times lower versus patients in Groups II and III. All patients with severe intoxication had symptoms of toxic hepatitis, which was manifested by a significant increase in ALT, AST, LDH and bilirubin, exceeding the normal limits by 5.4, 5.4, 1.8, and 1.7 times, respectively. Ammonia blood levels in patients with severe intoxication exceeded the norm by 5.6 times, in patients with moderate severity of intoxication – by 3 times, and even in patients with a mild degree – by 1.5 times. The lactic acid level in patients of Group I was 3.2 times above the norm, in patients of Groups II and III – 2.0 and 1.4 times, respectively. In patients with severe intoxication, there was an increase in blood levels of medium molecules over 0.6 units of optical density which reflected severe endogenous intoxication. Assessment of ANS parameters in patients of three groups revealed development of hypersympathicotonia due to the increased tone of the sympathetic department of ANS in proportion to intoxication severity. Cognitive functions at admission were inhibited in proportion to the severity of the patient's condition. Intelligence level as per MMSE scale: at admission, patients of Groups III and II demonstrated mild and moderate cognitive impairment (25.8 ± 2.1 and 23.31 ± 1.80 points); in Group I, indicators for all items were 1.5 times lower versus Groups II and III. Intelligence as per the FAB scale: in patients with severe intoxication, deviations in conceptualization and dynamic praxis were noted. The Reitan test results were best in patients from Group III. Subsequently, 63 (80.7%) patients with severe alcohol intoxication developed alcoholic delirium. Conclusion. Patients with alcohol intoxication demonstrated a decrease in cognitive functions and impaired intelligence proportional to the severity of intoxication and levels of lactate and free ammonia. Increased tone of the sympathetic division of the ANS is typical of acute alcohol intoxication during drinking bout. Cardiointervalography parameters can be used to assess the severity of alcohol intoxication.